An Update of Recent Use of Aegilops Species in Wheat Breeding - Kishii, Masahiro (Frontiers in Plant Science, 2019)
Aegilops species have significantly contributed to wheat breeding despite the difficulties involved in the handling of wild species, such as crossability and incompatibility. A number of biotic resistance genes have been identified and incorporated into wheat varieties from Aegilops species, and this genus is also contributing toward improvement of complex traits such as yield and abiotic tolerance for drought and heat. The D genome diploid species of Aegilops tauschii has been utilized most often in wheat breeding programs. Other Aegilops species are more difficult to utilize in the breeding because of lower meiotic recombination frequencies; generally they can be utilized only after extensive and time-consuming procedures in the form of translocation/introgression lines. After the emergence of Ug99 stem rust and wheat blast threats, Aegilops species gathered more attention as a form of new resistance sources. This article aims to update recent progress on Aegilops species, as well as to cover new topics around their use in wheat breeding.